Experimental Investigation of Phase Change inside a Finned-Tube Heat Exchanger. (8th October 2014) - Rahimi, M.; Ranjbar, A. A.; Ganji, D. D.; Sedighi, K.; Hosseini, M. J.
Abstract : An experimental study is conducted in order to investigate melting and solidification processes of paraffin RT35 as phase change materials in a finned-tube. Therefore the effect of using fins in this study as well as some operational parameters is considered. The motivation of this study is to design and construct a novel storage unit and to compare it with a finless heat exchanger. A series of experiments are conducted to investigate the effect of increasing the inlet temperature and flow rate on the charging and discharging processes of the phase change material. It is shown that, using fins in phase change process enhances melting and solidification procedures. The trend of this variation is different for the heat exchangers; increasing the inlet temperature for the bare tube heat exchanger more effectively lowers melting time. Similarly, flow rate variation varies the solidification time more intensely for the bare tube heat exchanger.